Transgender and Gender Diverse (TGD) Asian Americans in the United States: Experiences of Violence, Discrimination, and Family Support - Lerner, Justin E. (Journal of interpersonal violence, 2022)
Transgender and gender diverse (TGD) Asian Americans in the U.S. have multiple stigmatized identities, yet their experiences of violence and discrimination are not well understood. We utilized the 2015 United States Trans Survey, the largest survey to date with U.S. TGD people, to study the experiences of TGD Asian Americans. Our study included 699 TGD Asian Americans who experienced violence and discrimination in the form of unequal treatment, verbal harassment, and physical attack. We assessed how experiences differed by sociodemographic characteristics, including birthplace, income, age, education, disability, gender identity, and region. We also explored how family support was associated with experiences of violence in the sample. Bivariate analyses and multivariable regressions were used to understand how sociodemographic variables and family support are linked to experiences of violence and discrimination. Results indicated that income, age, disability, gender identity, and family support are significantly associated with violence and discrimination. As TGD Asian Americans currently experience high levels of violence and discrimination due to transphobia and a rapidly rising anti-Asian bias stemming from the COVID-19 pandemic, efforts to better understand factors that may increase vulnerability and identify how family support can mitigate those experiences are imperative.